Solid waste management in the mining industry in Ghana: a case study of Ashanti Goldfields Company Limited Obuasi, Ghana - Boachie, Williams Kwasi (2011)
A thesis submitted to the Department of Economics and Industrial Management, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Arts degree in Economics, 2003